1995
DOI: 10.2169/internalmedicine.34.992
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of an Acute Spontaneous Spinal Epidural Hematoma without Neurological Deficits.

Abstract: A 46-year-old womanpresented with sudden severe pain in the interscapular region. Physical examination, including detailed neurological evaluation, did not disclose any abnormalities.However, magnetic resonance imaging revealed an epidural hematomaanterior to the thoracic spinal cord and its spontaneous resolution thirty days after onset. Her hospital course was uneventful. To our knowledge, this report documents the first case ofa spontaneous spinal spidural hematomawithout neurological deficits. Spinal epidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
0
28
1
1
Order By: Relevance
“…Some authors [4,17,27,35,38] have reported that the conservative treatment is effective, but the standard management is a quick diagnosis and evacuation of hematoma by a surgical operation [2,6,13,18,21,24,28,32,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors [4,17,27,35,38] have reported that the conservative treatment is effective, but the standard management is a quick diagnosis and evacuation of hematoma by a surgical operation [2,6,13,18,21,24,28,32,34].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several case reports where the clinical state and the radiological findings improved within a few hours of the symptom onset [4,17,18,21,27,38]. However, it was mostly mild or benign cases were treated conservatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current case the major cause may have been the undulating abdominal pressure (occurring when the patient was using the toilet) combined with anticoagulant therapy using a Factor Xa inhibitor and antiplatelet effect due to ibuprofen. Urgent decompression was indicated because the best outcomes can be expected when surgery is performed within 24 h or, ideally, within 12 h [10]. Only a small number of cases have been reported where complete recovery was achieved by conservative treatment [11,12], although there remains the possibility for SSEH to resolve spontaneously.…”
Section: Case Reportmentioning
confidence: 99%
“…Acute chest or cervical pain followed by sensory or motor deficits has been suggested to be a strong indicator of the presence of SEH 6 . Serizawa et al 7 described a case of SEH characterized by intense back pain but without neurological deficits.…”
Section: Casementioning
confidence: 99%